The N-glycosylation at positions 652 and 661 of viral spike protein negatively modulates porcine deltacoronavirus entry - Wang, Hai-Ming; Qiao, Yang-Yang; Liu, Yong-Gang; Cai, Bing-Yan; Yang, Yue-Lin; Lu, Hui; Tang, Yan-Dong (Frontiers in Veterinary Science, 2024)
N-glycosylation is a highly conserved glycan modification that plays crucial roles in various physiological processes, including protein folding, trafficking, and signal transduction. Porcine deltacoronavirus (PDCoV) poses a newly emerging threat to the global porcine industry. The spike protein of PDCoV exhibits a high level of N-glycosylation; however, its role in viral infection remains poorly understood. In this study, we applied a lentivirus-based entry reporter system to investigate the role of N-glycosylation on the viral spike protein during PDCoV entry stage. Our findings demonstrate that N-glycosylation at positions 652 and 661 of the viral spike protein significantly reduces the infectivity of PDCoV pseudotyped virus. Overall, our results unveil a novel function of N-glycosylation in PDCoV infection, highlighting its potential for facilitating the development of antiviral strategies.